PERAN TEGAKAN SENGON DI HUTAN TANAMAN INDUSTRI DALAM MITIGASI PERUBAHAN IKLIM GLOBAL (The Role of Sengon’s Stand at Forest Plantation in Global Climate Change Mitigation) - Junaedi, Ajun; Rizal, Moh (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2019)
This research aims to estimate the biomass, carbon storage, carbon dioxide uptake and oxygen produced by sengon (Paraserianthes falcataria (L.) Nielsen) stand aged 9, 11 and 13 years in IUPHHK-HTI PT Parwata Rimba, Central Kalimantan. Estimated of biomass, carbon stock, CO2 uptake and Oxygen produced using allometric equations. The results showed that the storage of sengon standing biomass aged 9,11 and 13 years ranged from 110.71 to 200.94 tons/ha, carbon stock ranged from 52.03 to 94.44 tons C/ha, CO2 uptake ranged from 190.79 to 259.13 tons CO2/ha and Oxygen produced around 138.75 to 251.84 tons O2/ha. The total of biomass, carbon stock, CO2 uptake and Oxygenproduced by sengon stands at forest plantations are large enough to have an important role in global climate change mitigation in the forestry sector.